Prediksi Komitmen Organisasi Berdasarkan Faktor Karakteristik Pegawai, Faktor Psikologis, Dan Faktor Retensi Pada Aparatur Sipil Negara Di Provinsi Kepulauan Riau - Widijaya Widijaya (Faculty of Economics, Universitas Internasional Batam, 2018)
Law of Republic Indonesia number 5 of 2014 on the civil state personnel was a government reform in realizing high quality of human resources. Organizational commitment reflects the attitude of empathy towards the organization and the willingness to participate with the organization in the long run. The sample of this research is civil state personnel from government cities/regencies department in Riau Archipelago. Total of 500 questionnaires were distributed but only 457 being collected. This research used multiple regressions in analysis data with IBM SPSS Statistics 22. This research focused on examining the effect of characteristic factors, psychological factors, and retention factors on organizational commitment.The result of this research showed that psychological capital, perceived organizational support, job satisfaction, job characteristics, and work/life policies have a significant positive influence towards organizational commitment. Age, marital status, tenure, education level, job scope, compensation, training and development opportunities, supervisor support, and career opportunities show no significant influence towards organizational commitment.